Ergenlerin Akrana Bağlanma Stillerinin Umutsuzluk Düzeyleri İle İlişkisinin İncelenmesi / Examining the Correlation of the Peer-Attachment Styles with Hopelessness Levels in Adolescents - Kanak, Mehmet; Bilbay, Asuman; Balta, Dursun (Journal of History Culture and Art Research, 2017)
ABSTRACT The purpose of this study is to examine the correlation between the peer attachment styles and hopelessness levels in adolescents. The research was a descriptive study based on correlational survey model. The population of the study consisted of a total of 213 students studying in the 6th, 7th, and 8th grades of Erzincan Otlukbeli Fatih Secondary School, and the 9th, 10th, 11th, and 12th grades of Otlukbeli Multi-program Anatolian High School. The data were collected by using the “Beck Hopelessness Scale” (BHS) developed by Beck, Lester and Trexler (1974) to determine the hopelessness levels of the students, and the “Adolescent Friendship Scale” (AFS) developed by Wilkinson (2008) and adapted into Turkish by Ercan (2015) in order to determine the peer attachment styles of adolescents. As a result of the analyses carried out in order to determine the hopelessness levels of the participants based on gender and level of teaching, it was observed that there was no significant difference on hopelessness levels in terms of gender (p>.05); on the other hand, the hopelessness scores of high school students were higher compared to secondary school students in terms of level of teaching (p<.05). The peer attachment styles of the participants in terms of gender and level of teaching were determined by using t test. As a result of these analyses, it was observed that there was no significant difference in the subscales of attachment styles in terms of gender (secure, avoidant, anxious/ambivalent) (p>.05), there was a significant difference between the mean scores obtained by the secondary school students from Secure Attachment and Avoidant Attachment subscales of the Adolescent Friendship Scale in terms of level of teaching (p<.05); and there was no significant difference between their mean scores of Anxious/ambivalent Attachment subscale (p>.05). Pearson Product-Moment Correlation test was used for examining the correlation between peer attachment styles and hopelessness levels of the participants. As a result of the analysis, it was observed that while there was a negative significant correlation between total score of hopelessness level and the secure attachment subscale (p<05), there was no significant correlation between total score of hopelessness level and avoidant and anxious/ambivalent attachment subscales of the participants (p>05). As a result of the study, recommendations were offered to the researchers and the staff members working in the field in accordance with the results obtained. ÖZ Bu çalışmanın amacı; ergenlerin arkadaşa bağlanma stilleri ile umutsuzluk düzeyleri arasındaki ilişkinin incelemesidir. Araştırma ilişkisel tarama modeline dayalı betimsel bir çalışmadır. Araştırmanın çalışma grubu, Erzincan Otlukbeli Fatih Ortaokulu’nda öğrenim gören 6., 7., 8. sınıf ve Otlukbeli Çok Programlı Anadolu Lisesi’nde öğrenim gören 9., 10., 11. ve 12. sınıf olmak üzere toplamda 213 öğrenciden oluşmaktadır. Veriler; öğrencilerin umutsuzluk düzeylerini belirlemek için Beck, Lester ve Trexler (1974) tarafından geliştirilen “Beck Umutsuzluk Ölçeği’’ (BUÖ) ve ergenlerin arkadaşa bağlanma sitillerini belirlemek için Wilkinson (2008) tarafından geliştirilen, Türkçe’ye uyarlama çalışması Ercan (2015) tarafından yapılan “Ergenler İçin Arkadaşa Bağlanma Ölçeği” (EİABÖ) kullanılarak toplanmıştır. Katılımcıların cinsiyetine ve öğretim kademesine göre umutsuzluk düzeylerini belirlemek için yapılan analizler sonucunda cinsiyete göre umutsuzluk düzeyinde anlamlı bir farklılık bulunmadığı (p>.05), ancak öğretim kademesine göre lise öğrencilerinin ortaokul öğrencilerine göre umutsuzluk puanlarının daha yüksek olduğu (p<.05) görülmüştür. Katılımcıların cinsiyeti ve öğretim kademesine göre arkadaşa bağlanma stillerini belirlemek için t testi kullanılmıştır. Yapılan bu analizler sonucunda, cinsiyete göre bağlanma stilleri alt boyutlarında (güvenli, kaçınan, kaygılı/kararsız) anlamlı farklılık olmadığı (p>.05), öğretim kademesine göre ise ortaokul öğrencilerinin Ergenler İçin Arkadaşa Bağlanma Ölçeği Güvenli Bağlanma alt boyutu ve Kaçınan Bağlanma alt boyutlarında aldıkları puan ortalamaları arasında anlamlı bir farklılık olduğu (p<.05) görülürken; Kaygılı/Kararsız Bağlanma alt boyutundan aldıkları puan ortalaması arasında anlamlı bir farklılık bulunmadığı (p>.05) görülmektedir. Katılımcıların arkadaşa bağlanma stilleri ve umutsuzluk düzeyleri arasındaki ilişkinin incelenmesinde Pearson Momentler Çarpımı testi kullanılmıştır. Yapılan analiz sonucunda umutsuzluk düzeyi toplam puanı ile güvenli bağlanma alt boyutu arasında negatif yönde anlamlı bir ilişki olduğu görülürken (p<05); katılımcıların umutsuzluk düzeyi toplam puanları ile kaçınan ve kaygılı/kararsız bağlanma alt boyutları arasında anlamlı bir ilişki bulunamamıştır (p>05). Araştırmanın sonucunda, elde edilen bulgular doğrultusunda araştırmacılara ve alanda çalışan meslek elemanlarına öneriler sunulmuştur.